The Synergy of Hamka's Thought in Tafsir Al-Azhar with the Profile of Pancasila Students - Maftuhah Husnaeni; Muhammad Rafiiy; Fikri Hamdani; Darlis Darlis (Jurnal Iman dan Spiritualitas, 2026)
This study aims to analyze the epistemological convergence and construct a non-dichotomous synergy model between Buya Hamka's thought on character education in Tafsir Al-Azhar and the six dimensions of the Pancasila Student Profile within the Merdeka Curriculum. The key concepts revolve around adabi ijtima'i exegesis, tawhidic unity, and the re-conceptualization of civic virtues as expressions of transcendental devotion. Utilizing a qualitative library research design combined with hermeneutic interpretive techniques (systematic, linguistic, teleological, and philosophical) and comparative analysis, the research rigorously examines the thirty-volume primary corpus of Tafsir Al-Azhar alongside national curriculum policy documents. The main findings reveal that all six dimensions of the Pancasila Student Profile—faith and piety, global diversity, mutual cooperation, independence, critical reasoning, and creativity—possess profound theological grounding in Hamka's exegesis, where tawhid serves as the ultimate metaphysical anchor directing modern 21st-century competencies. The primary methodological challenge involved bridging the gap between classical exegetical discourse and contemporary technocratic policy frameworks without diluting spiritual depth. The practical implications offer strategic guidance for policymakers, curriculum designers, and educators to operationalize a character education model that is deeply rooted in indigenous religious scholarship yet responsive to global disruptions. This research contributes an innovative, non-dichotomous theoretical architecture for character education that bridges the historical divide between religious ethics and national civic schooling in Indonesia by revitalizing local exegetical heritage.